Kristologi Multikultural Bagi Penguatan Budaya Toleransi Mahasiswa Kristen: Sumbangsih Materi Bagi Mata Kuliah Agama Kristen di Perguruan Tinggi - Jimmy Rungkat (Jurnal Sosial dan Teknologi Terapan AMATA, 2023)
This research aims to understand the teachings and life of Jesus Christ as a person present in the midst of cultural diversity (Multicultural Christology) as a contribution to the material of tolerance in the Christian Religion courses at the College for strengthening the culture of student tolerance. Through qualitative descriptive methods through hermeneutic-exegesis approaches the result is obtained that Multicultural Christology teaches that Christ must be present in the midst of diversity, Christ is always associated with “the other” not sin but the duty of showing love and bringing peace, Christ always promotes a reconciliation mission that touches human issues, Christ willing to learn about “the others”, and Christ always carries out a mission of dialogue in a spirit of solidarity. Starting from this, it is implemented in the strengthening of a culture of Christian students’ tolerance, namely the awareness of being present in the midst of diversity, the consciousness of willingness to learn about “the others”, the conscience of carrying out a mission of dialogue, and the constipation to live side by side with “the other” in thinking and acting in order to provide solutions and service to human social problems.